Anatomical and chemo-taxonomical investigations within some Salsola L. species grown in the western costal region of Egypt - Taia, Wafaa K.; A.Shiha, Mona; Al-Kogali, Aisha A.; Abd-Almaged, Amani M. (International Journal of Scientific Research and Management (IJSRM), 2018)
Fourteen stem anatomical characters, beside twelve minerals; Na,Mg,Al,Si,P,S,Cl,K,Ca,Fe,Cu,Zn; and organic matters ;flavonoids,Kaempherol, quercetin, quercetin-3-glucoside, quercetin-3-rhamnoside and quercetin-3-rutinoside; were identified in six Salsola species; S.inermis, S.kali, S.longifolia,S tetragona.,S. tetrandra and  S.volkensii  grown in the Mediterranean coastal strip from Alexandria to El-Dabaa district in Egypt, in order to better understanding of the relations between the studied species and elucidate the arguments about their taxonomic position. The work based on light microscope for anatomical investigations, X-ray analyses in the leaves for minerals compositions and paper chromatography in all plant parts for chemical organic constituents. The anatomical results obtained showed that S. kali  and S. innermis are closely related  and separated from the rest of the studied species, while S.tetrandra and S.volkensii are related as well and meanwhile in relation with the other two species;S.tetragona and S.longifolia .These characters revealed that the genus exhibit abnormal secondary growth with variations within the studied species.. The mineral contents in the leaves of these species differs between the taxa. The maximum records of  Mg, Al. Si, P, Ca, and Fe were found in S. kali While the maximum records in Na and K were found in S.inermis. Flavenoids, Kaempherol, quercetin, quercetin-3-glucoside, quercetin-3-rhamnoside and quercetin-3-rutinoside identified. No flavone aglycons and glycosides or C-glycosides were detected. Hypogallic acid, gallic acid, phloroglucinol, gentisic acid, protocatchuic acid and -(-)epicatchin have been also detected. The biochemical data indicate that Salsola kali is highly different and support its anatomical aspects. Mineral and organic compounds analyses revealed that the studied species are under stress and their variations cannot be used in the taxonomy of the group. All the obtained results indicate that S.kali has its own characters which support its separation in a separate section as indicated by previous authors